Independence Character Level of Social Sciences Education Students in University of Riau - M. Yogi Riyantama Isjoni; Nurdiansyah; Naila Fauza; Ahmal; Eka Yanuarti; Reka Amelia Lestari (Corolla International Conference, 2022)
Education is the main element in forming character, especially in the attitude of independence of a learner. The character of independence is an attitude that must be possessed by a learner, because it has indicators of an important role, namely an attitude of initiative, viewing obstacles as challenges, and always having targets in the learning process in achieving achievements in lectures. The purpose of this study was to determine the level of independence of Social Sciences Education Department students. This study uses a quantitative form that aims to provide answers to the intent which in this case is a descriptive study presented using tables and diagrams. responses to the questionnaire were prepared based on 4 levels of the Likert Scale. The population of this study were active students majoring in Social Studies Education which consisted of the Study Programs of Economic Education, Pancasila Education and Pancasila and Citizenship Education, and History Education. The research sample was selected using the Stratified Random Sampling Technique approach, with an active number of 15% odd semester students. As a result, independent character indicators get a score of 87%